Barriers in implementing the green building concept in greater Kuala Lumpur - Chew, Li Wei (2023)
This paper investigates the barriers to implementing the green building concept in Greater Kuala Lumpur. The study aims to determine the relationship between internal and external factors that influence the development of the green building concept in Malaysia, identify the most challenging factors across industry players in Greater Kuala Lumpur, and propose strategies to encourage industry players to adopt the green building concept in the future. The research involved 100 respondents and revealed that various factors create a barrier to the development of the green building industry in Malaysia. The study recommends that all stakeholders in the construction industry take responsibility for promoting green building practices, including architects, property agents, the government, universities, and customers. Creating an ecosystem where all stakeholders work together can enhance the development of the green building industry in Malaysia and promote a sustainable environment while contributing to economic growth.